Bandung as a Creative City in Indonesia: The Role of Community in Developing a Creative Tourism Urban Village Initiative - Hermawan, Daniel (Research Synergy Foundation, 2024)
Bandung City Government, in collaboration with the Bandung City Culture and Tourism Office, has implemented the activation of creative tourism urban villages as a strategic measure to promote regional autonomy through the development of the creative economy. Prior studies have not extensively addressed the concept of creative tourism in urban villages as an alternative form of tourism. Therefore, this research aims to explore the involvement of communities in the management of creative tourism urban villages in Bandung, seeing them as the primary stakeholders. The objective of this study is to chart the potential and obstacles facing creative tourism urban villages in Bandung City from the perspective of tourism awareness groups as managers of creative tourism urban villages. The study employed qualitative methodologies with a phenomenological approach, specifically in-depth interviews with managers of creative tourism urban villages, as well as field observations of 8 activated creative tourism urban villages in Bandung city. The activation of creative tourism urban villages in the city of Bandung to promote the sustainable development goal is characterized by three primary themes: community dynamics, infrastructure readiness and external support. Community dynamics refers to the interactions that take place among community members as they collaborate to establish creative tourism urban villages in different regions through stories, conflicts and the active involvement of community members. The availability of infrastructure is contingent upon the presence of tangible assets that facilitate the execution of creative tourism urban village business operations, encompassing aspects such as road accessibility, parking availability, and building structures. Assistance from external entities refers to the support provided by external parties to foster the growth of creative tourism in urban villages, including mentoring, training, sponsorship, and collaboration networks. The activation of creative tourism urban villages needs to be accompanied by community independence and involvement in a bottom-up development process, not just a top-down one, so as to maintain the sustainability of creative tourism urban villages after the government no longer supports activities carried out by tourism awareness groups.